Voluntary emission reductions, social rewards, and environmental policy - Michael Rauscher (Fondazione Eni Enrico Mattei (FEEM), 1997)
Social norms and intrinsic motivations lead to voluntary environmentally responsible behaviour even in the absence of environmental policy. The paper shows that the introduction of environmental policy may lead to a reduction of voluntary abatement and sometimes may increase emissions and environmental damage. The explanation is that voluntary abatement is socially rewarded and the reward depends on the general attitude of society towards voluntary abatement. So, if the government tightens environmental standards, the voluntary component of abatement is reduced and the social reward is negatively affected. Some considerations concerning optimal environmental policies are discussed towards the end of the paper.
Keywords: A13; H30; Q28; 330